SAPAAN DALAM RANAH KEAGAMAAN ISLAM (ANALISIS SOSIOSEMANTIK) - Ening Herniti (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2014)
AbstractGreeting is a word used to greet, reprimand, or call the second personor addressees. Greetings can present the religiosity. The diction of forms in every language has different rules, because they also have different cultures and social backgrounds. Greetings in the field of religiosity are also different. The religious term is one of greeting form. This study is done using Sosiosemantics, the study focuses on the analysis of the meaning which is based on th social and culture. This paper describes how the forms of greeting are used in the community and how is the representation of the greeting in the community. The result of the analysis shows that the form of Islamic greeting mostly taken from Arabic, but there is not derived from Arabic, such as ajengan and kiai. Some of greeting in Islam is not only concerned with people who are experts Islam, but also with regard to religious representation. Greetings as the title of Islamic religious leaders are ulama, syekh, kiai, buya, ajengan, ustaz/ustazah, and dai/daiah. Greetings are used as a representation of a person in religious piety, for example, akhi, ukhti, ikhwan, akhwat, ana, and antum a word derived from the Arabic wordactually has neutral meaning. However, the usage of greeting only found in an exclusive Islamic community.Keywords: greetings, religious, Islam, social, socio-semantic.